The Effect of Electrical Passive Cycling on Spasticity in War Veterans with Spinal Cord Injury - Rayegani, Seyed M.; Shojaee, Hadi; Sedighipour, Leyla; Soroush, Mohammad Reza; Baghbani, Mohmmad; Amirani, Omm’Ol Banin (Frontiers in Neurology, 2011)
Introduction: Muscle atrophy, spasticity and deformity are among long term complication of Spinal Cord Injury(SCI) veterans. There are numerous studies evaluating effect of functional electrical stimulation (FES) on muscle properties of SCI people, but less research has focused on the benefits of passive cycling in the management of spasm and improving ROM of lower limbs in individuals with SCI. Aims: To evaluate the effect of electrical passive cycling on passive range of movement spasticity and electrodiagnostic parameters in SCI veterans. Methods: 64 SCI veterans referred to two clinical and research center in Tehran were recruited in this prospective clinical trial. The subjects were divided into 2 groups according to electrical passive cycling usage: 1) patients who didn’t use pedal exercise(control group), 2) patients used Electrical passive cycling up to optimal level (intervention group) . Main outcome measures included hip, knee and ankle rang of motion, spacticity scale, and electrodiagnostic parameters including F-Wave Consistency, F-Wave Amplitude, H/M Ratio, F/M Ratio, H Reflex Onset Latency and H Reflex Amplitude. Data were recorded at the time of receiving and one year after pedal exercise usage. Results : Sixty four SCI patients including 95.3% male, 4.7% female with mean age 43 years old were included in this study. All patients except one had complete SCI suffered from complete SCI. The involved spinal levels were cervical(17.2%), upper thoracic (34.4%), lower thoracic (45.3%) and lumbar (3.1%). Spasticity scale decreased significantly after passive cycling in group 2 and 3. Also hip, knee and ankle ROM in group 2 and 3 were significantly improved after pedal exercise. There was a significant difference in H max/M max (RT&LT) and F/M ratio after versus before electric passive cycling system in group 2. Conclusion: These findings suggest that passive rythmic leg exercise can lead to decrease in spasticity ,increase in passive ROM of low